Time Banking as an Alternative Social Movement: A Case Study of Time Banks in the United Kingdom - Garda Maharsi; Ahmad Ibrahim Badry; Puguh Sadadi (Ridwan Institute, 2023)
This research investigates dynamics of time banking as an alternative social movement against current conventional economic system. This research examines internal elements (motives, consolidation processes, and resource mobilizations) as well as external elements (campaign processes, social dynamics, and impacts) of Time Bank across United Kingdom. This research seeks to explain the dynamics of Time Bank as a multitude to become alternative for current conventional economy. This study uses case study approach, especially in United Kingdom. The method used in this study is qualitative method. Resource data obtained through interviews and literature studies. The research's purpose is: abstracting the dynamics of Time Bank across United Kingdom as a multitude, and then elucidates Time Bank's opportunities &; challenges for their future developments.